Performance of titanium salts compared to conventional FeCl3 for the removal of algal organic matter (AOM) in synthetic seawater: Coagulation performance, organic fraction removal and floc characteristics. (1st October 2017) - Chekli, L.; Corjon, E.; Tabatabai, S.A.A.; Naidu, G.; Tamburic, B.; Park, S.H.; Shon, H.K.
Abstract: During algal bloom periods, operation of seawater reverse osmosis (SWRO) pretreatment processes (e.g. ultrafiltration (UF)) has been hindered due to the high concentration of algal cells and algal organic matter (AOM). The present study evaluated for the first time the performance of titanium salts (i.e. titanium tetrachloride (TiCl4 ) and polytitanium tetrachloride (PTC)) for the removal of AOM in seawater and results were compared with the conventional FeCl3 coagulant. Previous studies already demonstrated that titanium salts not only provide a cost-effective alternative to conventional coagulants by producing a valuable by-product but also minimise the environmental impact of sludge production. Results from this study showed that both TiCl4 and PTC achieved better performance than FeCl3 in terms of turbidity, UV254 and dissolved organic carbon (DOC) removal at similar coagulant dose. Liquid chromatography – organic carbon detection (LC-OCD) was used to determine the removal of AOM compounds based on their molecular weight (MW). This investigation revealed that both humic substances and low MW organics were preferentially removed (i.e. up to 93% removal) while all three coagulants showed poorer performance for the removal of high MW biopolymers (i.e. less than 50% removal). The detailed characterization of flocs indicated that both titanium coagulants can grow faster, reach larger size and present a more compact structure, which is highly advantageous for the design of smaller and more compact mixing and sedimentation tanks. Both titanium coagulants also presented a higher ability to withstand shear force, which was related to the higher amount of DOC adsorbed with the aggregated flocs. Finally, TiCl4 had a better recovery after breakage suggesting that charge neutralization may be the dominant mechanism for this coagulant, while the lower recovery of both PTC and FeCl3 indicated that sweep flocculation is also a contributing mechanism for the coagulation of AOM. Graphical abstract: Highlights: We evaluate the performance of titanium coagulants for algal organic matter removal. Both titanium coagulants performed better than conventional iron salts. Humic substances and low molecular weight organics were preferentially removed. Titanium coagulants grow faster with higher floc size and more compact structure. Titanium coagulants had higher strength factor due to better organics adsorption.